Determinan Kinerja Keuangan Perbankan Syariah - Risal Ali Fatoni; Supami Wahyu Setiyowati; Doni Wirshandono Yogivaria (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study is to analyze the effect of profit sharing rate, Islamic Social Reporting (ISR), Mudharabah, Musyarakah, and Non-Performing Financing (NPF) on the profitability of Islamic banks in Indonesia. With a quantitative approach, this study focuses on six Islamic banks registered with the Financial Services Authority (OJK) during the period 2018 to 2023. Data analysis was conducted using the SamartPLS 4 method to test the direct, indirect, and moderation relationships between variables. The results show that the profit sharing rate and ISR have a positive effect on profitability, reflecting their role in increasing transparency and stakeholder trust. In contrast, Mudharabah and Musyarakah financing show a negative relationship to profitability, which is caused by the associated operational risks and challenges. In addition, NPF shows a significant negative impact, emphasizing the importance of effective risk management to maintain financial stability. This study is expected to provide benefits to the literature by integrating these variables into a comprehensive framework and providing an understanding of the various aspects that affect financial performance in Islamic banks. The results provide valuable implications for improving profitability and driving sustainable growth in the Islamic banking sector.